“To Sacrifice One’s Intellect Is More Demonic than Divine”: American Literature and Politics in Left Behind: A Novel of the Earth’s Last Days - Peter Swirski (European Journal of American Studies)
The article focuses on the cultural and political implication of the recent publishing sensation from two fundamentalist Christian ministers-turned-writers: Tim LaHaye and Jerry B. Jenkins. Their sixteen-book Left Behind Series (1995-2007) has by now sold close to eighty million copies, crossing over from the evangelical margins to the bookseller’s mainstream. Focusing by and large on the first novel in the series, the article analyzes its narrative and political logic in the context of the rise of apocalyptic imagery in American culture and public life.